Saliva-based methods for SARS-CoV-2 testing in low- and middle-income countries - Tan, Steph H.; Allicock, Orchid M.; Katamba, Achilles; Carrington, Christine V. F.; Wyllie, Anne L.; Armstrong- Hough, Mari (Bulletin of the World Health Organization, 2022)
As the coronavirus disease 2019 (COVID-19) continues to disproportionately affect low- and middle-income countries, the need for simple, accessible and frequent diagnostic testing grows. In lower-resource settings, case detection is often limited by a lack of available testing for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). To address global inequities in testing, alternative sample types could be used to increase access to testing by reducing the associated costs. Saliva is a sensitive, minimally invasive and inexpensive diagnostic sample for SARS-CoV-2 detection that is appropriate for asymptomatic surveillance, symptomatic testing and at-home collection. Saliva testing can lessen two major challenges faced by lower- and middle-income countries: constrained resources and overburdened health workers. Saliva sampling enables convenient self-collection and requires fewer resources than swab-based methods. However, saliva testing for SARS-CoV-2 diagnostics has not been implemented on a large scale in low- and middle-income countries. While numerous studies based in these settings have demonstrated the usefulness of saliva sampling, there has been insufficient attention on optimizing its implementation in practice. We argue that implementation science research is needed to bridge this gap between evidence and practice. Low- and middle income countries face many barriers as they continue their efforts to provide mass COVID-19 testing in the face of substantial inequities in global access to vaccines. Laboratories should look to replicate successful approaches for sensitive detection of SARS-CoV-2 in saliva, while governments should act to facilitate mass testing by lifting restrictions that limit implementation of saliva-based methods.
Keywords: Saliva-based methods; SARS-CoV-2 testing; Low- and middle-income countries